Raw materials consumption strategies in the South-Eastern coast Tierra del Fuego (Argentina) - Alvarez, Myrian Rosa (2017)
The Selection of Biotic and Abiotic Raw Materials in Hunter-Gatherers. Raw material consumption strategies in the south-eastern coast Tierra del Fuego (Argentina).Hunter-gatherer-fisher societies who inhabited the south-eastern Atlantic coast of Tierra del Fuego exploited a wide range of local raw-materials that includes, among others, metaphorfic rocks, schists, volcanic glasses and bones that exhibit different physical properties and qualities. The most common studies about technological practices have been focused on recognizing the interaction and the constraints between raw material quality and tool design or manufacturing techniques. However, tools were produced to cope with different problems arisen in the historical trajectories of human societies. Consequently, an accurate understanding of technological diversity, raw material selection and procurement cannot be separated from the dynamic and the context of use of ancient tools. The aim of this presentation is to discuss raw materials procurement and production strategies in relation to tool usage. For that purpose we studied ten assemblages retrieved in Late Holocene archaeological sites. We will focus on the economic practices that involved ?less valuable? lithic raw materials and bones to understand technological organization as well as human-environment interaction. Additionally, use-wear studies allow us to assess the role of biotic resources in hunter-gatherer economy and to identify the taphonomic processes that impacted on lithic and bone artifacts.